Nematode communities in irrigated and rainfed rice fields in Sukabumi Regency, West Java - Munif, Abdul; Sitanggang, Della; Fatimatuzzahroh, Fatimatuzzahroh; Mirsodi, Muhammad; Kusumawardhani, Amelia; Indiyanti, Nurul Fitria (Agrovigor, 2025)
Rice (Oryza sativa L.) is the main staple crop in Indonesia. This study aims to analyze the nematode communities found in irrigated and rainfed lowland rice cultivation areas and to identify nematodes associated with rice plants in Sukabumi Regency, West Java. Nematodes were extracted from soil using the centrifugal flotation method, root samples using a mist chamber, and leaf and seed samples using a modified Baermann funnel method. Nematodes were identified based on morphological characteristics. Nematode community analysis was conducted by calculating absolute population, diversity index, evenness, and dominance. Nematodes found in both irrigated and rainfed fields exhibited low diversity, low evenness, and high dominance. The nematodes in irrigated rice fields included genus Helicotylenchus, Rhabditis, Meloidogyne, Hirschmanniella, Tylenchorhynchus, Pratylenchus, and Aphelenchoides. Nematodes found in rainfed rice fields included Meloidogyne, Hirschmanniella, and Criconemella. Meloidogyne spp. was among the dominant nematodes in root and soil samples across various rice cultivation types and locations.